2016
DOI: 10.1097/mnh.0000000000000232
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation regulates fibroblast growth factor 23 production

Abstract: Purpose of review Fibroblast growth factor 23 (FGF23) is a hormone secreted by osteocytes and osteoblasts that regulates phosphorus and vitamin D homeostasis. FGF23 levels increase progressively in chronic kidney disease (CKD), and FGF23 excess might be a causal factor of left ventricular hypertrophy, CKD progression and death. Therefore, understanding the molecular mechanisms that control FGF23 production is a critical to design therapies to lower FGF23 levels. The present review focuses on the role of inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 92 publications
4
58
0
Order By: Relevance
“…Next, our analyses focused upon the interactions of heart failure and iron deficiency with plasma FGF23, while several other non-CKD-MBD regulators of FGF23 have been suggested, including the presence of inflammatory diseases [42]. However, at least within CARE FOR HOMe, adjustment for inflammatory markers did not modify our study results.…”
Section: Discussion/conclusionmentioning
confidence: 74%
“…Next, our analyses focused upon the interactions of heart failure and iron deficiency with plasma FGF23, while several other non-CKD-MBD regulators of FGF23 have been suggested, including the presence of inflammatory diseases [42]. However, at least within CARE FOR HOMe, adjustment for inflammatory markers did not modify our study results.…”
Section: Discussion/conclusionmentioning
confidence: 74%
“…The study suggested that HIF‐PHIs might enhance phosphate‐induced vascular smooth muscle cell calcification in CKD or ESRD patients with poorly controlled mineral bone metabolism . A molecular link also exists between HIF and FGF23 signaling, which may negatively impact cardiovascular risk in HIF‐PHI‐treated CKD patients . Another potential adverse effect that may be observed in CKD patients on HIF‐PHI therapy is hepatic toxicity.…”
Section: Hif‐prolyl Hydroxylases As Drug Targets In Renal Anemiamentioning
confidence: 99%
“…NFκB is the pivotal transcription factor in inflammatory processes . Previous studies have already established a clear role for inflammation in the synthesis of FGF23 . In detail, inflammatory cytokines have been shown to induce FGF23 production , and some acute and chronic inflammatory diseases are associated with an elevated serum FGF23 level .…”
Section: Discussionmentioning
confidence: 99%